Endoscopic management of Boerhaave syndrome: a comprehensive review of techniques, outcomes and future directions - Rivera Nájera, Sayra Karelia; Hernández Solís, Eduardo Ibrahim; García Cruz, Ethel Jenny (International Surgery Journal, 2024)
Boerhaave syndrome, characterized by spontaneous esophageal rupture, presents a critical condition requiring prompt diagnosis and intervention to reduce morbidity and mortality. Traditionally managed with surgical intervention, advancements in endoscopic techniques have emerged as viable alternatives, offering less invasive options with promising outcomes. This article provides a thorough review of the endoscopic management of Boerhaave syndrome, detailing the indications, techniques, and outcomes associated with various endoscopic approaches. We examine the role of esophageal stenting, clipping, and tissue sealants, alongside adjunctive therapies. Furthermore, we discuss patient selection criteria, procedural considerations, and potential complications. Our review highlights the evolving landscape of Boerhaave syndrome management, underscoring the importance of multidisciplinary collaboration and the need for further research to optimize patient outcomes.